SISTEM INFORMASI MANAJEMEN PENGADAAN IKAN EKSPOR BERBASIS WEB MENGGUNAKAN METODE EOQ DAN ROP - Novita andini (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The advancement of information technology plays an important role in improving the efficiency and accuracy of business processes, including in the fisheries sector. The company that serves as the object of this study is a marine product processing and export company that still manages raw material inventory manually, resulting in stock discrepancies and delays in the replenishment process. Therefore, this study aims to develop a web-based Export Fish Procurement Management Information System by integrating the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods to determine the optimal order quantity and automate reorder decisions. The research employed a quantitative approach using the waterfall system development model. The system was developed using native PHP with a modular architecture to support efficient web application development, while MySQL was utilized as the database management system to support centralized storage and integration of procurement data. The results show that the implementation of the EOQ and ROP methods provides optimal procurement recommendations for each type of fish. The highest EOQ value was obtained for Frozen Whole Tuna at 7,991 kg with an ROP of 986 kg, while Canned Crab recorded the lowest EOQ value of 1,239 kg with an ROP of 58 kg.